Pelatihan Budidaya Maggot untuk Pakan Ternak di Kelurahan Kastela, Ternate Selatan, Maluku Utara - Irmayanti, Laswi; Nurhikmah; Sulasmi; Wulansari, Angela; Dewi, Eka Kusuma; Fatrawana, Adesna (Jurnal Pengabdian Masyarakat Hutan, 2024)
Maggots are organisms in the second phase of the black soldier fly life cycle. Maggots move into the pupal phase which then turns into adult flies. Maggot (Hermetia illucens Linnaeus) is a black soldier fly larva that has a chewy texture, high protein, and has the ability to secrete natural enzymes that help improve the digestive system (Fauzi and Sari, 2018). The high level of nutrients contained in maggots, their abundant availability, their use which does not compete with humans and their easy-to-make growing media show good potential as an alternative combination of animal feed. The maggot cultivation training activity aims to train the younger generation to be able to participate in society in using maggots as an alternative animal feed. The activity was held on Monday 27 July 2020 to provide material and media creation which was attended by 18 participants. The care process until harvesting is monitored every week by the Community Service Team. Training activities are carried out in several stages, starting from preparing tools and materials, making media, the maggot cultivation process, and the harvesting process. It is hoped that maggots can be the answer to the problem of availability, namely the price of feed is cheap and easy to obtain, does not cause environmental pollution, and can increase the immune system of livestock. Keywords: cultivation, maggot, training